Perkembangan Keaksaraan Awal melalui Alat Permainan Edukatif Drawing Board pada Anak - Halifah, Syarifah (Jambura Early Childhood Education Journal, 2023)
This study aimed to stimulate early literacy through a drawing board educational game tool in the A RA UMDI group in Kampung Baru, Parepare City. Based on the problems seen by the researchers, some children were lacking in knowing and knowing the letters of the alphabet and could not distinguish between vowels and consonants and the children were unable to know the letters of their names. Based on this problem, the researcher intends to apply an educational game tool, namely a drawing board which is expected to stimulate early literacy development in children in group A. The indicators for assessing the game are based on STPPA, namely 1) pronouncing letters, 2) bolding letters, 3) imitating letters 4) children can recognize the letters of their names. The results showed that before the educational game tool was implemented some children did not know about the letters of the alphabet. After the researchers applied the educational game tool, there was an increase in children who previously did not know about letters became able to distinguish between vowels and consonants. From the results of these activities, the researcher concluded that there was an increase in the development of early literacy through the drawing board game in which all the assessment indicators increased.